Lateral line morphology in some gobiid species - Morales, Christian James C. (Iloilo University of the Philippines Visayas, 2020)
Fishes perceive local water motions and pressure differences through the Lateral Line (LL) system that is composed of sensory cells distributed in anatomically distinct patterns all over the body. Its morphology is important in the classification of gobioids and related species. Many factors affect morphological variation, such as the species and the prevailing hydrodynamic conditions in its habitat. In this study, the LL morphology in Trypauchen vagina, a burrower, Gymnogobius castaneus, a regular benthic goby, and Periophthalmus gracilis, an amphibious goby, were compared in terms of distribution, appearance, number, and sensory polarity. The abovementioned species are all members of the finfish family Godiidae but experience different hydrodynamic conditions and exhibit different behavioural patterns. All species examined had LL systems that are dominated by Superficial Neuromasts (SNs), and were distributed all over the body, except for T. vagina, which had none on its caudal fin. Most of the SNs in T. vagina and P. gracilis were either depressed in pits or developed directly on the skin or scale, while those in G. castaneus were sitting on epidermal protrusions. P. gracilis had 18 canal pores on the ventral portion of the head, while there was none on the other two species.
Thesis - M. S. Fisheries (Fisheries Biology) - Institute of Marine Fisheries and Ocean Sciences, College of Fisheries and Ocen Sciences, University of the Philippines Visayas.
Keywords: Gobiidae; Lateral line system; Gobioids